The year of Billy Miller - Henkes, Kevin (Greenwillow Books, an imprint of HarperCollinsPublishers, 2015)
Seven-year-old Billy Miller starts second grade with a bump on his head and a lot of worries, but by the end of the year he has developed good relationships with his teacher, his little sister, and his parents and learned many important lessons.